On peace education in Colombia: a grounded international perspective. Issue 3 (2nd September 2022) - Schultze-Kraft, Markus
ABSTRACT: Promoted by the peace process between the Santos administration (2010–2018) and the Revolutionary Armed Forces of Colombia, which resulted in the signing of a peace accord in November 2016, peace education at Colombia's higher education establishments and schools is gaining momentum. Educators have seized upon the opportunity afforded by the peace process and the associated legislation, particularly Law 1448 (2011) on victims and Law 1732 (2014) on the Peace Chair ( Cátedra de la Paz ), to energise peace education. Yet this is proving to be difficult. Among the challenges are the persistence of high levels of political, criminal and other types of violence following the termination of the armed conflict affecting learners' attitudes, behaviours and values; little relevance for peace education of established education in ethics and democratic citizenship competences; limited concrete knowledge on tertiary peace education as a pedagogical field; a vague legal framework; and little institutional guidance. Based on the author's first-hand experience as a conflict analyst and university lecturer in Colombia and a discussion of the 'conventional' and 'critical' orientations of peace education, this paper addresses these challenges and presents ideas on how tertiary peace education in Colombia could be enhanced through a focus on historical memory.